Impact Of Organizational Culture On Growth Of The Organization With Special Reference To Selected Manufacturing Units (International Journal of Food and Nutritional Sciences, 2022)
Organizational culture one of the significant and vital thing related with the employee job satisfaction as well as overall growth of the organization. The present research study dealt with the relationship between organizational culture and its impact on growth of the organization. In order to examine the relationship certain organizational culture practices have been identified and discussed from the employee as well as other stakeholder’s point of view. In order to examine the relationship between various aspects primary as well as secondary data used. findings of the study indicated that all the study instruments such as change management, job designing technique and training & development have significant impact on growth of the organization.